Settlement of Tax Disputes in the Russian Federation and Germany - A. A. Konyukhova (Vestnik MGIMO-Universiteta)
This article is devoted to the settlement of tax disputes in the Russian Federation and the Federal Republic of Germany. The features of the conflict settlement mechanism are both shown in the stage of administrative and judicial review. In accordance with German law, the administrative stage of dispute resolution, carried out by the tax authority, always precedes the filing of a complaint to a court. Consequently, the taxpayer submits his first application in writing to the tax authority that issued the tax act, though in some cases to a higher tax authority. This obligatory procedure was borrowed by the Russian tax system. The trial stage of tax dispute settlement in Germany is carried out by specialized courts, forming a two-level system for legal proceedings. Thus, the tax dispute submitted to the Court is settled first by the financial lands courts and then by the higher Federal Financial Court. However, the Federal Financial Court takes into consideration only certain categories of actions listed in the Act (the Regulations) of finance courts (Finanzgerichtordnung). In Russia appeals of administrative review of tax conflicts, unlike in the German system, are handled by arbitration and general jurisdiction courts. The Supreme Arbitration Court of the Russian Federation is the supreme judicial body for settling economic disputes and other cases considered by arbitration courts in implementing federal procedural judicial supervision over their activities and provides explanations regarding judicial practices. Arbitration courts established at the level of the Federation to resolve disputes involving commercial entities, e.g. enterprises and entrepreneurs, resolve the bulk of tax disputes. These courts are composed of specially created panels of judges known as bars, i.e. groups of judges who specialize in reviewing taxation cases.